Pengembangan Modul Ajar IPAS Kelas IV SD dalam Kurikulum Merdeka - Faradita, Meirza Nanda; Afiani, Kunti Dian Ayu (University of Muhammadiyah Malang, 2024)
This study is motivated by the fact that the number of teaching modules in the independent curriculum at the elementary school level is still applied to Grades I and IV, so many teachers are still confused about making teaching modules in the independent curriculum. Many teachers feel lazy when it comes to developing other than lesson plans, so researchers had the opportunity to develop teaching modules for class IV at the elementary school level as a guide and also a reference for teachers at SD Muhammadiyah 8 Surabaya. The study aimed to determine the validity, practicality, and effectiveness of fourth-grade teaching modules at the Merdeka Curriculum Elementary School. The research is used as a reference for teachers in making teaching modules in the independent curriculum, which, at this time, at Muhammadiyah 8 Surabaya Elementary School, is still transitioning from the 2013 curriculum to the independent curriculum. The method used in this study is the Borg and Gall model development research method. Data collection techniques are validation sheets, questionnaire sheets, and test sheets. The data analysis technique uses percentage, learning completeness, and average value and is categorized according to several valid, feasible, and practical criteria. The results of this development research explained that the teaching modules for class IV of Elementary School were said to be valid in the first validation and were said to be very valid in the second validation after product revisions were carried out, teaching modules for class IV Elementary School were also said to be very suitable for use in class IV Elementary School Muhammadiyah 8 Surabaya and were said to be very effective for students there.